2006
DOI: 10.1073/pnas.0511322103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin and Timothy syndrome increase mode 2 gating of CaV1.2 calcium channels through aberrant phosphorylation of S6 helices

Abstract: Calcium channels in the plasma membrane rarely remain open for much more than a millisecond at any one time, which avoids raising intracellular calcium to toxic levels. However, the dihydropyridinesensitive calcium channels of the CaV1 family, which selectively couple electrical excitation to endocrine secretion, cardiovascular contractility, and neuronal transcription, have a unique second mode of gating, ''mode 2,'' that involves frequent openings of much longer duration. Here we report that two human condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 32 publications
(35 reference statements)
2
116
0
Order By: Relevance
“…Furthermore, kinetic assays, with CaMKII␤ as kinase and GSK-3␣ or GSK-3␤ as substrate, were conducted to assess the kinetics of phosphorylation reactions as described previously (21) , respectively. As compared with the reported data for CaMKII phosphorylation of autocamtide (66) and for PKA phosphorylation of GSK-3␤ (21), the relatively low K m value for the in vitro phosphorylation of GSK-3 by CaMKII is consistent with both GSK-3␣ and GSK-3␤ acting as physiological substrates of CaMKII␤. We conclude from these data that CaMKII␤ phosphorylates GSK-3␣ and GSK-3␤ both in vivo and in vitro.…”
Section: Rsksupporting
confidence: 56%
“…Furthermore, kinetic assays, with CaMKII␤ as kinase and GSK-3␣ or GSK-3␤ as substrate, were conducted to assess the kinetics of phosphorylation reactions as described previously (21) , respectively. As compared with the reported data for CaMKII phosphorylation of autocamtide (66) and for PKA phosphorylation of GSK-3␤ (21), the relatively low K m value for the in vitro phosphorylation of GSK-3 by CaMKII is consistent with both GSK-3␣ and GSK-3␤ acting as physiological substrates of CaMKII␤. We conclude from these data that CaMKII␤ phosphorylates GSK-3␣ and GSK-3␤ both in vivo and in vitro.…”
Section: Rsksupporting
confidence: 56%
“…In addition to the IQ motif, another three CaM-binding sites, the preIQ region in the C-terminal tail (22,23), the NSCaTE motif in the N-terminal of Cav1(α 1 ) Ca 2+ channels (24), and I-II linker (26), have been identified. The complexes formed by CaM and each of these motifs might allow CaM to perform the two opposing processes of CDF and CDI.…”
Section: +mentioning
confidence: 99%
“…These phenomenons suggested that the endogenous CaM and CaMKII were perhaps washed out gradually, and they have different and closely related effects in the regulation of Ca 2+ channels. As mentioned above, there are at least four CaMbinding sites (22 -24, 26) and several CaMKII phosphorylation sites (26,34) in the Cav1.2 Ca 2+ channel. Therefore it is possible that CaMKII phosphorylates multiple sites and affects the multiple binding sites of CaM as inferred from Fig.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] In addition, residues located at the cytoplasmic end of IS6 have been reported to affect channel opening. [22][23][24] These residues seem to coincide with the bundle crossing region where S6 from other domains come together (reviewed by Hering, et al). 6 Thus, it appears coherent that the I-II linker adds a component to the channel gating machinery as it is physically connected to IS6 of the voltage-dependent ion channel family.…”
Section: Introductionmentioning
confidence: 99%